IN THE PRODUCTION OF SPORTS CLOTHING BASED ON INTERLOCK FABRIC (International Conference on Educational Discoveries and Humanities, 2025)
This scientific thesis studies the design processes of an enterprise specializing in the production of sportswear based on interlock fabric. During the study, the trends of the modern sportswear market, the technical characteristics and advantages of interlock fabric, and the technological and economic aspects of the enterprise project were analyzed. The designed enterprise has a production capacity of 100,000 pieces of sportswear (T-shirts, shorts, sweatshirts) per year and will achieve a self-pay indicator within 5 years. The study examined in detail the equipment, raw material base, jobs, and management system necessary for the enterprise located in Andijan. Special attention was also paid to the enterprise's compliance with environmental safety standards and the principles of sustainable development. As a result of the study, it was proven that the production of sportswear based on interlock fabric is a competitive and stable profitable project in the economy of Uzbekistan.